Implementasi Kegiatan Eksplorasi Alam dalam Mengembangkan Rasa Ingin Tahu Anak di Raudhatul Athfal: Implementation of Nature Exploration Activities in Developing Children's Curiosity at Raudhatul Athfal - Fitri Silaturahmi; Robiatul Adawiyah (AJMIE: Alhikam Journal of Multidisciplinary Islamic Education, 2026)
This study aims to describe the implementation of nature exploration activities in developing the curiosity of Group A children at RA An-Nur, located in Mentor Village, Probolinggo. This research employed a descriptive qualitative approach using observation, interviews, and documentation. The findings indicate that nature exploration provides direct learning experiences that effectively stimulate children’s curiosity through observing, questioning, discovering, and discussing. Children became more active in asking questions, showing exploratory interest, and communicating their findings to teachers and peers. The teacher played an essential role by providing guiding questions and support that encouraged critical thinking. Moreover, this activity positively influenced children’s language and social-emotional development. Therefore, nature exploration is proven to be an effective and relevant learning strategy for fostering curiosity in early childhood